Age-related differences in disease characteristics and clinical outcomes in polycythemia vera. Issue 9 (September 2013) - Stein, Brady L.; Saraf, Santosh; Sobol, Urszula; Halpern, Anna; Shammo, Jamile; Rondelli, Damiano; Michaelis, Laura; Odenike, Olatoyosi; Rademaker, Alfred; Zakarija, Anaadriana; McMahon, Brandon; Spivak, Jerry L.; et al.
Abstract: The natural history and prognosis for young patients with polycythemia vera (PV) in the post- JAK2 V617F era are not well defined. Therefore, we retrospectively analyzed disease characteristics and clinical outcomes in 120 patients ≤ 45 years and 84 patients ≥ 65 years at diagnosis. Despite lower white blood counts (9.2 vs. 13.4 × 10 9 /L, p = 0.004) and a lower JAK2 V617F allele burden (51% vs. 66%, p = 0.015), younger patients with PV had comparable rates of vascular complications compared to older patients (27% vs. 31%, p = 0.64). However, splanchnic vein thrombosis occurred more frequently in younger patients (13% vs. 2%, p = 0.0056). Myelofibrotic and leukemic transformation, the most serious complications of myeloproliferative neoplasms (MPN), occurred with similar frequencies in young versus older patients (15% vs. 10%, p = 0.29). Prevention or delay of these complications is currently the most urgent challenge in the care of younger patients with PV.